2007
DOI: 10.1891/0730-0832.26.3.161
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Six Sigma Methodology to Reduce Incidence of Breast Milk Administration Errors in the NICU

Abstract: Breast milk is the optimal source of nutrition for infants. According to research, neonates fed breast milk have a reduced risk of sepsis, increased feeding tolerance, a decreased incidence of necrotizing enterocolitis, and better neurodevelopmental outcomes. Unfortunately, researchers have not identified practices to reduce or eliminate the risk for errors in breast milk administration. This article discusses the potential hazards of incorrect administration of breast milk. It then describes how the tertiary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…Drenckpohl et al [5] described a remarkable and Dougherty and Giles [4] a transient reduction of breast milk administration errors after focused interventions. While Drenckpohl et al used the six sigma methodology to monitor and reduce the incidence of breast milk application errors, Dougherty and Giles developed a quality assurance (QA) program.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Drenckpohl et al [5] described a remarkable and Dougherty and Giles [4] a transient reduction of breast milk administration errors after focused interventions. While Drenckpohl et al used the six sigma methodology to monitor and reduce the incidence of breast milk application errors, Dougherty and Giles developed a quality assurance (QA) program.…”
Section: Discussionmentioning
confidence: 99%
“…Breast milk, the optimal source of nutrition for neonates, may contain pathogens and therefore carries the risk to transmit infections [4,5]. Namely, the human immunodeficiency virus, hepatitis virus, cytomegalovirus, herpes simplex virus, and methicillin-resistant Staphylococcus aureus can have harmful consequences for the neonate [9,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17] Potentially adverse outcomes may result from improperly labeled milk, unsuitable storage conditions, unsafe milk preparation, incorrectly fortified milk, and misadministration of human milk. 18,19 Drenckpohl et al 20 identified inconsistencies in the process for managing human milk storage, preparation, and distribution resulting in "Centralized handling of human milk is an important strategy to provide optimal quality care to patients and to assure safety in storage, preparation, and distribution of human milk for hospitalized infants. "…”
Section: Review Of Literaturementioning
confidence: 99%
“…75,76 In addition to system design to prevent such errors, barcoding systems have been developed, explored, and advocated 77 as a means of tracking and ensuring correct administration of human milk.…”
Section: Pediatric-specific Aspectsmentioning
confidence: 99%